2020
DOI: 10.1111/1365-2435.13565
|View full text |Cite
|
Sign up to set email alerts
|

Is it time to include legumes in plant silicon research?

Abstract: 1. To date, the functional role of plant silicon has mostly been investigated in grasses (Poaceae). This potentially overlooks the importance of silicon in other plant functional groups such as legumes (Fabaceae). Legumes form a symbiotic relationship with nitrogen-fixing bacteria (rhizobia) inside the root nodules for fixing atmospheric nitrogen. A small, but growing number of studies suggest that silicon promotes this symbiotic relationship.2. We consider how legumes may take up and deposit silicon relative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 116 publications
1
49
0
Order By: Relevance
“…Several transporters and genes that are involved in Si uptake and accumulation have been studied so far. Although the study of Si transporters focuses on rice and other grasses (as is commonly the case in plant Si research [ 5 , 18 ]), the first plant gene to regulate Si accumulation was discovered in the gourd Cucurbita (Cucurbitaceae), regulating Si and phytolith formation in the fruit rind [ 108 ]. Shortly after, a surge of discoveries of the physiology and genetics of Si uptake in grasses has arisen, revolving around the four Lsi transporters, all belonging to the NIP aquaporin family.…”
Section: Silicon Uptake By Plantsmentioning
confidence: 99%
See 3 more Smart Citations
“…Several transporters and genes that are involved in Si uptake and accumulation have been studied so far. Although the study of Si transporters focuses on rice and other grasses (as is commonly the case in plant Si research [ 5 , 18 ]), the first plant gene to regulate Si accumulation was discovered in the gourd Cucurbita (Cucurbitaceae), regulating Si and phytolith formation in the fruit rind [ 108 ]. Shortly after, a surge of discoveries of the physiology and genetics of Si uptake in grasses has arisen, revolving around the four Lsi transporters, all belonging to the NIP aquaporin family.…”
Section: Silicon Uptake By Plantsmentioning
confidence: 99%
“…Second, although the variability of Si content has a clear taxonomic signal, with orders accounting for 67% of the variation [ 172 ], phylogenetic analyses indicate great variations below the order level [ 23 ]. For example, most literature cites the grass family Poaceae and more generally the order Poales as being the most Si-rich, at least among angiosperms [ 18 , 172 , 173 , 174 ], which is in part why a large portion of plant Si research focuses on this family [ 5 , 18 ]. However, Poales is also the only commelinid order to date in which Si-poor families were observed (e.g., Typhaceae) [ 23 ].…”
Section: The Variability Of Silicon In Plantsmentioning
confidence: 99%
See 2 more Smart Citations
“…For this purpose, the different responses of Si-accumulating and non-accumulating species must be carefully considered when exposed to individual mineral stress, to build a general conclusion. Notably, as proposed by Putra et al [ 95 ] an extensive investigation needs to be considered on the cross-talk between Si and legumes to decipher how Si promotes the symbiotic relationship with nitrogen-fixing bacteria. This body of Si is crucial in the future works as numerous studies showed the positive interactive effect of Si and plant growth promoting rhizobacteria on plant growth particularly under unfavorable environmental conditions [ 96 ].…”
Section: Remark and Prospectivementioning
confidence: 99%